Konnichiwa's Advertising Model in an Effort to Reach Consumers (Case Study at Konnichiwa Japanese Restaurant, Bandung City) - Thalita Syifa Fatimah; Agus Rahayu; Puspo Dewi Dirgantari (Journal of Accounting and Finance Management, 2022)
Konichiwa is a Micro, Small and Medium Enterprises company that has a Japanese restaurant concept inspired by an Anime (Japanese cartoon). However, Konnichiwa restaurants are still not optimal in carrying out direct promotions or promotions through social media, so many people do not know about Konnichiwa restaurant stores. This study uses a qualitative descriptive type method, with collection using interviews and documentation techniques. The data analysis used was in the form of data reduction, data presentation, and drawing conclusions. The data validation technique uses triangulation techniques. The result of the research is to find that the advertising that Konnichiwa is currently doing is using social media advertising, advertising through banners, and events, and relying on (WOM) or word of mouth.